The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s40279-013-0028-y
|View full text |Cite
|
Sign up to set email alerts
|

What Do Athletes Drink During Competitive Sporting Activities?

Abstract: Although expert groups have developed guidelines for fluid intake during sports, there is debate about their real-world application. We reviewed the literature on self-selected hydration strategies during sporting competitions to determine what is apparently practical and valued by athletes. We found few studies of drinking practices involving elite or highly competitive athletes, even in popular sports. The available literature revealed wide variability in fluid intake and sweat losses across and within diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 83 publications
0
52
0
1
Order By: Relevance
“…However studies suggest that commencing exercise in a mild state of hypohydration is not uncommon across athletic populations (Garth and Burke 2013, Volpe et al 2009, Maughan et al 2005. Furthermore, it has been shown that many athletes fail to consume sufficient fluids during exercise to offset fluid loses, resulting in levels of dehydration in excess of 2% BM loss (Gore et al 1993, Kurdak et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…However studies suggest that commencing exercise in a mild state of hypohydration is not uncommon across athletic populations (Garth and Burke 2013, Volpe et al 2009, Maughan et al 2005. Furthermore, it has been shown that many athletes fail to consume sufficient fluids during exercise to offset fluid loses, resulting in levels of dehydration in excess of 2% BM loss (Gore et al 1993, Kurdak et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…training or match play) within cool environmental conditions (~12˚C) are effective at maintaining hydration to <2% BM loss (Garth and Burke 2013). However, it is apparent within these data that change in BM did not reflect the changes in POsm due to the observation of some BM loss arising without the occurrence of an increase in POsm (Table 1).…”
Section: Relationshipsmentioning
confidence: 85%
“…Comprehension of the mechanisms that regulate fluid balance in varying sporting and environmental situations is vital to ensure the implementation of appropriate hydration strategies. Typically during exercise in temperatures less than 25˚C, team sport athletes appear to lose between ~1% and 1.5% of pre exercise body mass (BM) (Garth and Burke 2013). This magnitude of BM loss is well within the 2% threshold often proposed to impair performance in high-intensity, intermittent sport (Judelson et al 2007), however inconsistencies surrounding this threshold are evident within the literature (Judelson et al 2007;Sawka et al 2007;Kraft et al 2012).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The beverages were made from sports drink (Gatorade, PepsiCo, New York, USA) and a commercial machine was used to make ice slurry (Sorby Dream 2, SPM Drink Systems, Spilamberto, Italy). The tepid fluid condition was designed to simulate common drinking practice among athletes and the ice slurry condition was designed to simulate the use of a pre-cooling strategy (Garth & Burke, 2013;Ihsan et al, 2010). During the ingestion period, participants sat on a massage table in an air-conditioned room (23˚C).…”
Section: Beveragesmentioning
confidence: 99%